1975
DOI: 10.1149/1.2134222
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Stabilization of Anodic Oxides on GaAs

Abstract: Anodic oxidation of GaAs is examined and a technique for growing full surface oxides ~ 86G,0A thick is reported. Anodization in a hot, concentrated (30%) H202 electrolyte of pH ~-2 using self-anodizing metal contacts is found to yield uniform oxides with a refractive index of 1.8 and a growth rate ranging from 22 to 50 A/V. The as-grown oxide will etch in HC1 and H20. Chemical stability of this oxide is enhanced with baking in dry nitrogen and after 2 hr at 250~ H20 will no longer etch the oxide; after 1 hr at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1975
1975
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, associated complexes of oxygen such as Si-O (13), VG~-O ( 14), etc., may play a role in the recombination efficiency in both the n-and p-layers of an LED. Evidence to support this hypothesis has been reported by a number of workers (15)(16)(17)(18). It is therefore clear that in order to improve the EL and generate purer spectra in green LED's all traces of oxygen must be removed from both the n-and p-layers.…”
Section: Introductionmentioning
confidence: 56%
“…However, associated complexes of oxygen such as Si-O (13), VG~-O ( 14), etc., may play a role in the recombination efficiency in both the n-and p-layers of an LED. Evidence to support this hypothesis has been reported by a number of workers (15)(16)(17)(18). It is therefore clear that in order to improve the EL and generate purer spectra in green LED's all traces of oxygen must be removed from both the n-and p-layers.…”
Section: Introductionmentioning
confidence: 56%
“…Since each polytype has a different energy gap (2.3-3.3 eV), SiC will be a useful semiconductor for various visible light emitting devices by a combination of polytypes and luminescent centers. A number of SiC light emitting diodes have been fabricated up to date, but their luminescent efficiencies have been low (1). One of the main causes is a high temperature process (above 2000~ usually used for the crystal growth and the impurity doping, which makes it difficult to obtain good crystals and control impurity doping.…”
mentioning
confidence: 99%
“…After the anodic oxidation of GaAs, a gray or granular texture has been observed by Logan et al (3) and Spitzer et al (4) on n-type bulk GaAs, whose carrier concentration was 0.5 ~ 5 X 10~: cm -3, and on p-type bulk GaAs, whose hole concentration was 1 ~ 5 X 10 is cm-3, when they were oxidized in H202. Hasegawa et al (5) reported pits which spread from the fringe of the sample toward the inner area.…”
mentioning
confidence: 84%
“…The compositions of the samples have been analyzed by LEIS. The diameter of the scattering ion beam was 1 mm, the ion current ,~100 nA, and the scattering angle 142 ~ A detailed description of the ion-scattering equipment has been given elsewhere (4). Quantitative data for Ag and A1 were obtained by calibration against the pure elements.…”
Section: Methodsmentioning
confidence: 99%